Field trial on a novel control method for the dengue vector, Aedes aegypti by the systematic use of Olyset® Net and pyriproxyfen in Southern Vietnam - Tsunoda, Takashi (BioMed Central, 2013)
BACKGROUND: Jars, tanks, and drums provide favorable rearing/breeding sites for Aedes aegypti in Vietnam. However, the use of insecticides to control mosquitoes at such breeding sites has not been approved in Vietnam since they are also often sources of drinking water, making larval vector control difficult. Mosquito nets pre-treated with long-lasting insecticide treated nets (LLITNs) form an effective measure for malaria control. We examined changes in the abundance of immature Aedes aegypti to evaluate the efficacy of covering ceramic jars with lids comprising one type of LLITN, Olyset® Net, in inhibiting oviposition by adult females, and to evaluate the effect of treating other breeding containers, such as flower vases, inside and around the outside of houses with a slow-release pyriproxyfen formulation to kill pupae. METHODS: We selected 313 households for the trial and 363 households for the control in Tan Chanh, Long An province, Vietnam. In the trial area, Olyset® Net lids were used to cover five major types of water container (ceramic jars, cylindrical concrete tanks, other concrete tanks, plastic drums, and plastic buckets), while pyriproxyfen was used to treat flower vases and ant traps. We also monitored dengue virus transmission by measuring anti-dengue IgM and IgG levels in healthy residents in both control and trial areas to estimate the effectiveness of Olyset® Net at controlling the dengue vector, Aedes aegypti. RESULTS: The container-index and house-index for immature Ae. aegypti fell steeply one month after treatment in the trial area. Lids with Olyset® Net that fit container openings clearly seemed to reduce the presence of immature Ae. aegypti as the density of pupae decreased 1 month after treatment in the trial area. Pyriproxyfen was also effective at killing pupae in the water containers in the trial area. Although the dengue seroconversion rate was not influenced by Olyset® Net, it was lower in two-five year old children when compared to older children and adults in both control and trial areas. CONCLUSIONS: Our study showed that the treatment by Olyset® Net and pyriproxyfen had a strong negative effect on the prevalence of immature Ae. aegypti, which persisted for at least 5 months after treatment.